Advanced glycation end products are associated with sarcopenia in older women: aging marker dynamics. (4th May 2021) - Eguchi, Yawara; Toyoguchi, Toru; Inage, Kazuhide; Fujimoto, Kazuki; Orita, Sumihisa; Suzuki, Miyako; Kanamoto, Hirohito; Abe, Koki; Norimoto, Masaki; Umimura, Tomotaka; Koda, Masao; Furuya, Takeo; et al.
ABSTRACT: The aim of this study was to determine whether advanced glycation end products (AGEs) revealed by skin autofluorescence (SAF), serum and urine pentosidine level, and serum homocysteine level can serve as a biomarker for sarcopenia in older women. The participants were 70 elderly women. The AGEs pentosidine, homocysteine, and SAF were measured as aging markers. This study shows that among the biomarkers for aging, serum pentosidine correlates with a loss of appendicular lean mass and can serve as a biomarker for sarcopenia. Moreover, SAF and homocysteine values exhibited a positive correlation with age and correlated with each other. Abbreviations : AGEs: advanced glycation end products; BIA: bioelectrical impedance analyzer; BMD: bone mineral density; DLS: degenerative lumbar scoliosis; DXA: dual-energy X-ray absorptiometry; ELISA: enzyme-linked immunoassay; HHcy: hyperhomocysteinemia; RIA: radioimmunoassay; SAF: skin autofluorescence; SMI: skeletal muscle mass index; T2DM: type 2 diabetes patients